PENERAPAN INFORMATION TECHNOLOGY ETHICS DALAM PROSES BELAJAR MAHASISWA - Herlawati Herlawati (Cakrawala - Jurnal Humaniora, 2010)
Many research on Information Technology (IT) Ethics for ethical guidance when students graduate or the technical delivery (asinkron or direct course). But in reality, sometimes we found confused students when implement IT ethic as a result of inconsistent thins when they learn. Ethics of copyright, for example, is the contrast in the library on campus copying without permission of books (most of the overseas issue). Or some professors who share module copyright campus when teaching at other colleges. Although the meaning of "in order to enlighten the people" but in terms of ethics of course that it violates. Most of this is happening due to the angle of view that distinguishes between the college campus with the professional world that sometimes allows things to happen on the campus ethical violation (the reason for the nations') as long as not done the work (the professional world). Moreover,  the number of industrial policies (such as Microsoft ®) that does cut the price of its software with a particular reason (with a certain purpose, such as the introduction and strengthening brand products). Up to reinforce the reasons that campuses (including schools) different from the world of professional and community. In this paper will be presented several arguments that break the way the world should be distinguished college and the work with the principles of competency.Key Words : IT Ethics, Competency Based Curriculum,  E-learning.